LIVESTOCK CULTURE IN RURAL COMMUNITIES: AN ETHNOGRAPHIC STUDY OF TRADITIONAL FARMERS - Sudarto, Sudarto; Muhtadin, Muhtadin (Tahta Media Group, 2026)
This study aims to analyze the cattle-farming culture within traditional farming communities in Boyolali using an ethnographic approach. The research focuses on farming practices, the principle of moral economy, and the negotiation between traditional values and market logic in shaping rural socio-economic transformation. A qualitative method was employed through participant observation, in-depth interviews, and documentation. Informants were purposively selected from small-scale, family-based dairy farmers. The findings reveal that farming practices are not solely oriented toward profit maximization but are grounded in principles of household sustainability, community solidarity, and subsistence security. Modernization through milk quality standards, production technologies, and market integration has influenced production patterns; however, values such as mutual cooperation, family labor, and ecological integration remain preserved. The transformation of farming culture in Boyolali is hybrid and adaptive, where tradition and market rationality continuously negotiate to form a contextual and resilient production system. This study highlights the importance of socio-cultural perspectives in understanding sustainable rural livestock development.